The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/v15020365
|View full text |Cite
|
Sign up to set email alerts
|

Human Hematopoietic Stem Cell Engrafted IL-15 Transgenic NSG Mice Support Robust NK Cell Responses and Sustained HIV-1 Infection

Abstract: Mice reconstituted with human immune systems are instrumental in the investigation of HIV-1 pathogenesis and therapeutics. Natural killer (NK) cells have long been recognized as a key mediator of innate anti-HIV responses. However, established humanized mouse models do not support robust human NK cell development from engrafted human hematopoietic stem cells (HSCs). A major obstacle to human NK cell reconstitution is the lack of human interleukin-15 (IL-15) signaling, as murine IL-15 is a poor stimulator of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…In the absence of antibody treatment, mice became viremic, reaching an average PVL of 2.2x10 7 copies/mL at day 11. As previously reported (41, 82), viral replication was associated with a loss of peripheral CD4+ T cells. Treatment with 3BNC117 WT significantly reduced viral replication and partially restored CD4+ T cell levels in peripheral blood and several tissues, while A32 failed to do so (Figure 7B,C,D).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In the absence of antibody treatment, mice became viremic, reaching an average PVL of 2.2x10 7 copies/mL at day 11. As previously reported (41, 82), viral replication was associated with a loss of peripheral CD4+ T cells. Treatment with 3BNC117 WT significantly reduced viral replication and partially restored CD4+ T cell levels in peripheral blood and several tissues, while A32 failed to do so (Figure 7B,C,D).…”
Section: Resultssupporting
confidence: 84%
“…Briefly, NOD.Cg- Prkdc scid IL2rg -/- Tg(Hu-IL15) (NSG-15) hu-mice engrafted with human peripheral blood lymphocytes (hu-PBL) were infected with the primary isolate HIV-1 JRCSF (Figure 7A). This hu-mice model was previously shown to support HIV-1 replication and antibody Fc-effector function in vivo (24, 82). Infected hu-mice received nnAb A32 administered subcutaneously (S.C.) at day 6 and 9 post-infection (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…SS modeling studies by Poglio et al (2021) , van der Fits et al (2012) and Wu et al (2021) reported the generation of a limited number of SS PDX models that are encumbered by complex transplantation techniques (intrafemoral or intrahepatic engraftment), low engraftment efficiencies, and/or lack of skin or peripheral blood involvement. More recently, another immunodeficient strain expressing transgenic IL-15, NSG-IL-15, was reported ( Abeynaike et al, 2023 ). Both NSG-IL-15 and SRG15 strains appear to exhibit physiological levels of human IL-15 expression, and human CD34 + constitution results in similar NK cell frequencies in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Il2rg tm1.1Flv Tg(SIRPA), harbors humanized knock-in alleles M-CSF, IL-3/GM-CSF and TPO, and supports improved innate responses and myeloid differentiation [ 221 ]; NSG-SGM3 (NOD-scid IL2Rg null -3/GM/SF), carries human IL-3, GM-SF and CSF and allows stable myeloid lineage engraftment [ 222 , 223 , 224 ]; NSG-Tg(hIL34) carries humanized IL-34 and allows the improved engrafting of microglial cells [ 225 ]; NSG-Tg (hIL15) carries humanized IL-15 and allows improved Treg and natural killer cell development [ 226 , 227 ]; NSG-A2 expresses human HLA class I A2 molecule supports development of A2 restricted human T cells [ 228 ]; and DRAG, which are NOD.Rag1KO.IL2RccKO mice that express HLA-DR4 (0401), shows improved B cell and IgG reconstitution [ 229 ].…”
Section: Current Approaches To Modeling Pathogenesis and Studying The...mentioning
confidence: 99%